Uniting The Past and Future: Technology-Based Strategies to Nurture Cultural Identity - Djufri, Djufri; Arifin, Ansar; Basir, Muhammad (PT Mattawang Mediatama Solution, 2025)
The management of public spaces in Makassar faces challenges in maintaining a balance between modernization and the preservation of local cultural values. This study explores the role of local wisdom, especially the values of Siri' na Pacce, cooperation, and communal solidarity, in maintaining the sustainability of public spaces amid rapid urbanization. Using a qualitative ethnographic approach, this study conducts participatory observations, in-depth interviews, and document analysis to understand social dynamics in the management of public spaces. The results of the study show that despite changes due to urbanization, people still maintain cultural values in the use of public spaces. However, privatization and commercialization threaten community involvement in its management. Changes in social interaction patterns are also seen with the increasing use of digital platforms compared to physical meetings in public spaces. This research recommends culture-based strategies for more inclusive urban planning, by strengthening collaboration between governments, communities, and the private sector to ensure that public spaces remain part of society's social identity. Thus, local wisdom can continue to be the main pillar in maintaining the sustainability of public spaces in Makassar.